Implementation of Shariah Business Principles in Family Companies: A Case Study of Family MSMEs in the Special Region of Yogyakarta - Ahmad Sumiyanto (Hemispheres Press, 2026)
Family businesses play a dominant role in the economic landscape of the Special Region of Yogyakarta (DIY), Indonesia. This study aims to examine how Islamic business principles are implemented in the governance and operational practices of family businesses in DIY, as well as to identify the challenges and sustainability strategies associated with their implementation. Employing a qualitative approach with a case study method, the research involved owners and managers of three Sharia-compliant family-owned micro, small, and medium-sized enterprises (MSMEs) in DIY. Data were collected through in-depth interviews, observations, and document analysis, and subsequently analyzed using thematic analysis. The findings reveal that the implementation of Islamic business principles is reflected in three main dimensions: a commitment to muamalah contracts that are free from riba (usury), gharar (uncertainty), and maysir (gambling); the adoption of an Islamic work culture emphasizing compliance with halalan tayyiban principles; and the integration of spiritual values into leadership succession planning. The findings also challenge the common perception that adherence to Sharia principles constrains business growth. Instead, Sharia compliance enhances stakeholder trust and strengthens customer loyalty. This study contributes to both theory and practice by providing insights into the integration of Islamic values within the governance of local family businesses, offering a framework for promoting sustainable and ethically grounded business development.